2015
DOI: 10.1093/mnras/stv2276
|View full text |Cite
|
Sign up to set email alerts
|

Is 4U 0114+65 an eclipsing HMXB?

Abstract: We present the pulsation and spectral characteristics of the HMXB 4U 0114+65 during a Suzaku observation covering the part of the orbit that included the previously known low intensity emission of the source (dip) and the egress from this state. This dip has been interpreted in previous works as an X-ray eclipse. Notably, in this Suzaku observation, the count rate during and outside the dip vary by a factor of only 2-4 at odds with the eclipses of other HMXBs, where the intensity drops upto two orders of magni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 41 publications
4
19
0
Order By: Relevance
“…It is lower in the beginning of the observation, when the absorption is higher. These values are consistent with those found by (Pradhan et al 2015) using Suzaku. The spectral index α remains constant and <1, indicating an efficient Comptonising process (see Table A.1).…”
Section: Epic Spectrumsupporting
confidence: 92%
See 3 more Smart Citations
“…It is lower in the beginning of the observation, when the absorption is higher. These values are consistent with those found by (Pradhan et al 2015) using Suzaku. The spectral index α remains constant and <1, indicating an efficient Comptonising process (see Table A.1).…”
Section: Epic Spectrumsupporting
confidence: 92%
“…The observations were carried out in the time interval between 21-05-2015 20:43:19 UT MJD = 57 163.8634 and 22-05-2015 10:01:53 UT, corresponding to an average orbital phase φ ≈ 0.7 (using a P orb = 11.5983 d and the ephemeris of Pradhan et al 2015), which covers approximately 5% of the orbit. Our XMM-Newton observation was performed well outside the minimum in the long-term light curve (see Pradhan et al 2015 for Suzaku observations performed during the minimun). The data can be found in the XMM archive under the ID 0764650101.…”
Section: Observations and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Hainich et al (2020) showed that there was no systematic difference between the stellar properties in classic SgXBs and in SFXTs, hinting at similar wind micro-structures (Driessen et al 2019). Finally, Pradhan et al (2018) concluded that the higher variability of the emission in SFXTs compared to SgXBs was likely due to mechanisms inhibiting accretion near the accretor, rather than direct clump capture, although flares in SFXTs have recently been found by Ferrigno et al (2020) to be associated with massive structures approaching the accretor. To summarize, X-ray variability is, at best, an indirect tracer of the clumpiness of the wind because of intermediate regions where the clumps are mixed and where other instabilities can kick in, in particular those associated to the different accretion regimes.…”
Section: Introductionmentioning
confidence: 86%